2018
DOI: 10.30660/afinla.69700
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming methodological challenges in text production research: a holistic approach through data triangulation

Abstract: Text production research tends to analyse corpora of text products as its data. However, for the aim of investigating especially text production processes, such an approach falls short; a written text does its best to hide any traces of its genesis. This article argues for a holistic approach in text production research by presenting five methodological guidelines for future research: 1) what/how-research questions need to be followed by why-questions, and such research frameworks require 2) several methods to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…However, recent production-oriented research on journalistic quoting in a written format (e.g. Havumetsä, 2020;Kuo, 2007;Matsushita, 2016, in press;Nylund, 2006;Satoh, 2001), to which my series of studies (Haapanen, 2011(Haapanen, , 2016(Haapanen, , 2017a(Haapanen, , 2017b(Haapanen, , 2017c(Haapanen, , 2018(Haapanen, , 2020Haapanen and Perrin, 2019) makes a not inconsiderable contribution, has revealed that the relationship between original interview discourse 2 and the published quoted discourse is by no means so simple and simplistic. To begin with, there is no absolute correspondence between sound waves in the air and graphemes on paper or on screen, and several features of oral communication, such as prosody, do not have any apparent equivalence in writing -if any at all.…”
Section: Quoting: a Seemingly Clear And Simple Phenomenonmentioning
confidence: 99%
“…However, recent production-oriented research on journalistic quoting in a written format (e.g. Havumetsä, 2020;Kuo, 2007;Matsushita, 2016, in press;Nylund, 2006;Satoh, 2001), to which my series of studies (Haapanen, 2011(Haapanen, , 2016(Haapanen, , 2017a(Haapanen, , 2017b(Haapanen, , 2017c(Haapanen, , 2018(Haapanen, , 2020Haapanen and Perrin, 2019) makes a not inconsiderable contribution, has revealed that the relationship between original interview discourse 2 and the published quoted discourse is by no means so simple and simplistic. To begin with, there is no absolute correspondence between sound waves in the air and graphemes on paper or on screen, and several features of oral communication, such as prosody, do not have any apparent equivalence in writing -if any at all.…”
Section: Quoting: a Seemingly Clear And Simple Phenomenonmentioning
confidence: 99%
“…As my data I re-analysed two corpora that document the production processes of Finnish news items written for print and/or online media and of Swiss television news items. These corpora share a process-oriented approach to the study of newswriting and document both the material activities and the mental decision-making involved in newswriting (for a discussion, see Haapanen 2018). Besides the published media items, they also consist of recordings of journalistic interviews, editorial meetings, and workplace discussions, of semi-structured interviews, and of journalists' retrospective verbalisations of their writing processes.…”
Section: The Study: Modelling Quoting In Newswritingmentioning
confidence: 99%
“…Capturing writing processes has long been methodologically challenging (Haapanen 2018). Grésillon and Perrin (2014) have explained this problem by using a double black box metaphor.…”
Section: Next Step: Operationalising the Modelmentioning
confidence: 99%
See 2 more Smart Citations